KELEMBAGAAN GAPOKTAN MANGGIS DALAM MENGHADAPI PASAR MEA - CHARINA, ANNE; KUSUMO, RANI ANDRIANI BUDI; MUKTI, GEMA WIBAWA (Jurnal Social Economic of Agriculture, 2017)
MEA market is a great opportunity for our farmers. One commodity that is likely to be competitive in the MEA market is mangosteen. In fact, various problems faced by Gapoktan to plunge into the free market MEA. This study tried to assess the problems faced by Gapoktan Arta Mukti in the face of the MEA market and looking for problem-solving strategies faced. The method used is descriptive survey, with respondents 30 members Gapoktan Arta Mukti. Soft Systems Methodology used to analyze the problem and produce a conceptual model Gapoktan institutional improvement. The results showed there were many constraints faced by farmers' groups in the face of the MEA level of motivation among farmers to compete in the MEA is still lacking, the availability of ICT is not yet supporting, international networking has not been formed. But on the other hand the farmer has a carrying capacity of which has been certified organic and GHP as an important factor in commodity Manggis a prerequisite for entry into the free market. To prepare gapoktan jump directly to the required socialization MEA MEA, Quality Supervision, ICT Applications and Preparation of international networks.